AKTIVITAS SGOT, SGPT DI PENDERITA LUKA BAKAR SEDANG DAN BERAT - Sri Nurul Hidayah; Mutmainnah .; H. Ibrahim Abd. Samad (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
Burn injury is a kind of trauma with the high mortality and morbidity rate that needs special treatment since the very first phaseup to the end. this study targeted medium to severe burns, limited to liver complications. the objective of this study is to calculate andobserve the difference Sgot, SgPt activities in medium and severe burns. the Methods of this study was Cross Sectional, we conductedon 42 subjects with medium to severe burns, Hospitalised during the period of June 2005 to May 2007 at DR.Wahidin Sudirohusodohospital of Makassar. the data were calculated and statistically analysed using the SPSS V.11.5. We obtained of 12 (28.6%) mediumburn injuries and 30 (71.4%) severe burn injuries. In medium burn subjects the got showed normal activities in 6 subjects (50%) andhigh activities in 6 subjects (50%), the gPt showed normal activities in 8 subjects (66,7%) and high activities in 4 subjects (33.3%).In severe burn subjects the got showed normal activities in 6 subjects (20%) and high activities in 24 subjects (80%), the gPt showednormal activities in 13 subjects (43.3%) and high activities in 17 subjects (56.7%). there was no significant difference in the increasingactivities of Sgot and SgPt in either medium or severe burns, where p > 0.05. Increased activities of SgPt and Sgot was higher insevere burns than in medium ones. It was also obtained that increasing Sgot activities was found more often than SgPt in patientswith either medium or severe burns.